Association of physical exercise and calcium intake with bone mass measured by quantitative ultrasound - Galanos Antonios; Trovas Georgios; Paspati Ioanna; Dionyssiotis Yannis; Lyritis Georgios P (BMC, 2010)
Abstract Background Interventions other than medications in the management of osteoporosis are often overlooked. The purpose of this study was to investigate the association of physical activity and calcium intake with bone parameters. Methods We measured the heel T-score and stiffness index (SI) in 1890 pre- and postmenopausal women by quantitative ultrasound (QUS) and assessed physical activity and dietary calcium intake by questionnaire. Participants were divided according to their weekly physical activity (sedentary, moderately active, systematically active) and daily calcium consumption (greater than or less than 800 mg/day). Results SI values were significantly different among premenopausal groups (p = 0.016) and between sedentary and systematically active postmenopausal women (p = 0.039). QUS T-scores in systematically active premenopausal women with daily calcium intake > 800 mg/day were significantly higher than those in all other activity groups (p < 0.05) independent of calcium consumption. Conclusions Systematic physical activity and adequate dietary calcium intake are indicated for women as a means to maximize bone status benefits.